Clinical Utility of the DriveFocus™ Intervention on Young Drivers With and Without Experience - Alvarez, Liliana; Classen, Sherrilene; Medhizadah, Shabnam (Frontiers in Public Health, 2019)
Introduction. The DriveFocus™ intervention addresses the ability of young drivers to detect and respond to critical roadway information. DriveFocus is an interactive video-based tablet application that teaches users how to detect and prioritize critical roadway items. However, young drivers with and without experience may respond differently to the intervention. Objectives. We compared the simulated driving performance of two 17 year-old licensed drivers with (novice) and without (learner) driving experience, after three (post-test 1) and six (post-test 2) intervention sessions. Methods: We collected clinical, driving performance (number of visual scanning, adjustment to stimuli, and total driving errors) and acceptability data. Results. The learner driver made more visual scanning, adjustment to stimuli and total errors when compared to the novice. Both participants exhibited a decrease in both types and number of driving errors from baseline to post-test 2 and the learner also made less driving errors at post-test 1. Both participants rated the perceived ease of use of the intervention favorably. Conclusions: This study lays the foundation to examine the impact of the DriveFocus™ intervention among novice and more experienced young drivers.